Sensehacking passenger wellbeing while in the air - Spence, Charles (Frontiers in Future Transportation, 2023)
Air travel has undoubtedly become a more stressful activity for many passengers in recent years, in part as a result of the global Covid pandemic. Consequently, there has been a growing focus on how to optimize the psychological well-being of passengers while in the air. This narrative historical review considers how the passenger experience can potentially be hacked through the more intelligent stimulation of the travellers' senses. In particular, the focus is on promoting passenger comfort, enhancing the provision of healthy food and beverage options/experiences, facilitating relaxation and sleep and, when appropriate, boosting passengers' arousal/alertness as well (e.g., prior to arrival). A number of concrete suggestions concerning how to sensehack passenger well-being at the various stages while in the air are made.